The Concept of Dai in The Ummi Aminah Movie - Attika Zenit (Faculty of Ushuluddin and Dakwah, UIN K.H. Abdurrahman Wahid Pekalongan, Central Java, Indonesia, 2022)
Dai in the world of da'wah is essential, because without the presence of dai Islamic messages will not reach mad'u. Moreover, the dai are also ordinary people who do not escape from sin and experience trials from Allah SWT. Like the Ummi Aminah movie, it tells the story of a famous dai who has thousands of worshipers, especially women. Ummi Aminah is also the wife of Abah and has seven children. Ummi Aminah's journey as a preacher was not easy when Allah was testing her life. It starts with Zarika being caught in love with her coworker (Ivan) who is already married. Zaenal is imprisoned for drug cases. Risma's relationship - Umar's wife - is not harmonious with Ummi Aminah's family. Based on that background, the researcher formulated the problem, namely: how is the concept of dai depicted in the character of Ummi Aminah in the Ummi Aminah film? Ummi Aminah's film research method uses qualitative methods and descriptive research types. The analysis is John Fiske's semiotics, describing codes at the level of reality, representation, and ideology. The results of this study indicate that the concept of the dai depicted in the character of Ummi Aminah in the Ummi Aminah film has benefits as a benchmark for the dai described by Ummi Aminah in terms of understanding, requirement, and characteristics through film media.